2004
DOI: 10.1042/ba20030111
|View full text |Cite
|
Sign up to set email alerts
|

Engineering conduits to resemble natural vascular tissue

Abstract: Research on the use of biomaterials as vascular substitutes has been dominated in the past by studies focusing on the properties of the materials used. These need to be resistant to protein absorption and should allow cell colonization and integration of the biomaterial within recipient tissue. Despite promising perspectives related both to the appearance of new synthetic materials with biomedical applications and to developments in arterial replacement techniques, there are still many unresolved problems. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 137 publications
0
22
0
Order By: Relevance
“…The study also discovered that successive waves of neutrophils moving towards an infected foreign body became successively less effective in their ability to kill microorganisms. Finally, deposition of adherence proteins, such as albumin, fibrinogen, Hageman factor, high-molecular-weight kininogen, fibronectin, laminin, thrombospondin, collagen and immunoglobulins, on IVC surfaces [33] together with attachment of bacterial cells result in altered IVC surface conditioning, which promotes receptor-mediated attachment of microorganisms. The biomaterials used in IVC manufacture also affect host protein deposition and subsequent bacterial attachment, colonisation, biofilm formation and infections.…”
Section: Effect Of Intravascular Catheter (Ivc) Materials On Ivc-relamentioning
confidence: 99%
“…The study also discovered that successive waves of neutrophils moving towards an infected foreign body became successively less effective in their ability to kill microorganisms. Finally, deposition of adherence proteins, such as albumin, fibrinogen, Hageman factor, high-molecular-weight kininogen, fibronectin, laminin, thrombospondin, collagen and immunoglobulins, on IVC surfaces [33] together with attachment of bacterial cells result in altered IVC surface conditioning, which promotes receptor-mediated attachment of microorganisms. The biomaterials used in IVC manufacture also affect host protein deposition and subsequent bacterial attachment, colonisation, biofilm formation and infections.…”
Section: Effect Of Intravascular Catheter (Ivc) Materials On Ivc-relamentioning
confidence: 99%
“…However, their clinical utility is limited by potential immunogenic responses and the origin of suitable vessels. 2 Recently, synthetic grafts, such as woven poly(ethylene terephthalate) (Dacron) and extended polytetrafluoroethylene, have also been used for vascular reconstruction, but these grafts tend to fail when they are applied to small-diameter vessels because of their poor biocompatibility. 3,4 With the development of tissue engineering, blood vessel tissue engineering has emerged as a promising approach for addressing the shortage of current therapies.…”
Section: Introductionmentioning
confidence: 99%
“…9 The present study demonstrates that ␣ 2 (VIII) collagen is a potent attachment factor for ECs, significantly enhancing EC retention both in vitro and in vivo. In addition, we have identified that EC attachment to recombinant ␣ 2 (VIII) substrata occurs via the ␣ 2 ␤ 1 integrin.…”
Section: Discussionmentioning
confidence: 81%